PENGARUH GOOD CORPORATE GOVERNANCE, BUDAYA ORGANISASI DAN PENGEDALIAN INTERN TERHADAP KINERJA ORGANISASI DENGAN AKUNTABILITAS PUBLIKSEBAGAI VARIABEL INTERVENING (Survey Terhadap Rumah Sakit di Kota Padang) - Rora Aprilia; Emrinaldi Nur DP; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Hospital is an unic and compleks organization for its extensive use of human resources, features and charachteristics in its process to provide medical services. Majority of Hospitals in Indonesia have already been shifted to be of profit oriented rather than public service oriented. This research was conducted with a purpose of analyzing the direct effect of good corporate governance, organizational culture, and internal control toward organizational performance and undirect effect of good corporate governance, organizational culture, and internal control toward organizational performance which is mediated by public accountability so that in the future this research could be of used for promoting especially hospital performance and generally organizational performance. This research was conducted at 25 hospitals in Padang city with 75 respondents. The analytical methods that was used in this research is helped by Smart PLS software.The result was concluded as the good corporate governance, internal control, and public accountability has direct influence toward organizational performance. Nonetheless, organizational culture variable does not has influence toward organizational performance. The influence of good corporate governance, organizational culture, internal control, was significantly affecting the organizational performance through public accountability.Keywords: good corporate governance, organizational culture, internal control, public accountability, and organizational performance.